The utilization of tilting-filter photometry in airglow and auroral research - Dore, Ian Stuart (Rhodes University, Faculty of Science, Department of Physics and Electronics, 1992)
This thesis describes the application of tilting-filter photometry to the study of the airglow and aurora. Previous South African photometric research is reviewed. Optical instrumentation and techniques used in airglow and auroral research are reviewed. The transmission characteristics of narrowband interference filters are discussed. The analogue meridian-scanning tilting-filter photometry system used at Sanae, Antarctica is described. Shortcomings of this system have been identified, and modifications have been made to improve its spatial and temporal resolution. Details are given of the computer-controlled digital photometry system which replaced the analogue system. Equations are derived for the conversion of raw photometric data (analogue chart deflections or digital photon counts) to absolute emission intensities. The accuracy of the intensities obtained depends on the absolute calibration of the photometer, the transmission characteristics of the filter used to isolate the spectral feature of interest, and the effects of atmospheric extinction and scattering. The influence of these factors on observed emission intensities is discussed. Various models used to determine atmospheric correction factors are reviewed. It is shown that atmospheric correction factors can have a significant effect on both emission intensities and intensity ratios. The procedure used to determine the transmission characteristics of interference filters is described, as is the procedure used to cross-calibrate secondary light sources. The transmission characteristics of the filters and the brightnesses of the light sources were both found to have changed appreciably with age. The observation of a magnetospheric substorm at Sanae (L â‰ƒ 4) is used to illustrate the use of a meridian-scanning tilting-filter photometer system in auroral research. The ratio I(557.7)/ I(391.4) observed at Sanae was found to be lower than expected, as were the OJ airglow emission intensities. A prototype digital photometer system was used aboard a ship, to observe the airglow in the region of the South Atlantic Anomaly. Significant Nâ‚‚â º lNG emissions at 391.4 nm were measured, confirming the presence of discernable particle precipitation in the region. The 0I557.7 and 630.0 nm intensities measured from the ship were found to be lower than expected. This, combined with low airglow and auroral intensities measured at Sanae, is a cause for concern. It is recommended that further checks be made regarding the brightness of the calibration sources.
Keywords: Photometry -- Research; Airglow -- Research; Auroras -- Research; Auroral photography -- Research